Glycaemic status and reperfusion injury in patients with ST-segment elevation myocardial infarction. (14th October 2021) - Reindl, M; Lechner, I; Tiller, C; Holzknecht, M; Rangger, A; Mayr, A; Theurl, M; Klug, G; Brenner, C; Bauer, A; Metzler, B; Reinstadler, S J
Abstract: Background: Failed myocardial tissue reperfusion due to microvascular injury despite successful culprit lesion percutaneous coronary intervention (PCI) is associated with poor clinical outcome in patients with ST-elevation myocardial infarction (STEMI). A possible influence of dysglycaemia on myocardial reperfusion injury is unclear. Objectives: To investigate the association between glycaemic status and microvascular injury determined by magnetic resonance imaging in STEMI patients. Methods: This prospective observational cohort study included 260 consecutive STEMI patients undergoing primary PCI between 2016 and 2019. Peripheral venous blood samples for glucose and HbA1c measurements were drawn on admission. Primary microvascular injury endpoint was defined as presence of intramyocardial haemorrhage (IMH) assessed by cardiac magnetic resonance T2* mapping at 4 (interquartile range [IQR]:2–5) days after PCI. Results: HbA1c (odds ratio [OR]: 1.73 [95% CI: 1.24–2.40]; p=0.001), pre-diagnosis of diabetes (OR: 2.63 [95% CI: 1.18–5.90]; p=0.02) and glucose concentration (OR: 1.01 [95% CI: 1.00–1.01]; p=0.01) significantly predicted IMH, which was present in 90 (35%) patients. Of these three parameters, only HbA1c remained significantly associated with IMH (OR: 2.12 [95% CI: 1.12–3.99]; p=0.02) after adjusting for total ischemic time, culprit lesion location, pre- and post-interventional TIMI flow and peak biomarker concentrations (troponin, N-terminal pro-B-type natriuretic peptide and C-reactive protein). The rate of IMH was 24% in patients with HbA1c <5.7%, 43% in patients with HbA1c ≥5.7 to 6.4% and 59% in patients with HbA1c ≥6.5% (p<0.001). Conclusions: In STEMI patients undergoing primary PCI, admission HbA1c was independently associated with reperfusion injury as determined by IMH. These findings suggest that IMH could represent the underlying pathophysiological link between dysglycaemia and adverse outcomes following STEMI. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): FWF - Austrian Science Fund; ÖKG - Austrian Society of Cardiology